Evaluating ocean carrier selection criteria: Perspectives of Tasmanian shippers - Peter Dzakah Fanam; Leigh Ackerly (Journal of Shipping and Trade (JST), 2019)
The purpose of this paper is to evaluate the decision process of Tasmanian shippers when selecting an ocean carrier. Data collected through an internet-based survey is described, and influential selection criteria are reported with the use of exploratory factor analysis. The findings indicate that Tasmanian shippers are both price and service conscious. Tasmanian shippers, unlike their mainland Australian counterparts, have an overwhelming reliance on maritime transportation. The exploratory factor analysis indicates that service takes precedence over price for the subjects of the study. The findings indicate that network and schedule reliability and corporate social responsibility are influential in the choice of ocean freight services. Cargo security and seasonal capacity availability are similarly influential to Tasmania shippers. The study provides insight into the decision-making process of Tasmanian shippers. In this function, it may benefit Tasmanian ocean freight service providers by describing the characteristics that Tasmanian shippers find desirable in selecting between competing carriers. Thus, ocean freight service providers can formulate necessary strategies to attract Tasmania shippers to purchase their liner services.
Keywords: 650; Shippers; Tasmania freight; Freight forwarders; Ocean carriers; Selection criteria; Container service; Price attributes; Service attributes